Discovery and evaluation of anti-cancer agents - Lam, Fong Ki (2010)
Cancer is the most common cause of the human death in the UK. Every year 3.2 million Europeans are diagnosed with cancer, and the figure is projected to rise due to the aging population. Although significant advances are being made in the fight against the disease, cancer remains a key public health concern and a tremendous burden on UK society in financial and social terms. This thesis evaluated two classes of compounds that can be potentially developed as anti-cancer agents. 4-(4-Methyl-2-(methylamino)thiazol-5-yl)-2-(4-methyl-3-(morpholinosulfonyl)phenylamino)pyrimidine-5-carbonitrile (S-134, 5g) is a novel cyclin-dependent kinase 9 (CDK9) inhibitor showing nano-molar growth inhibitory potentials in established human cell lines. Biochemical assays have confirmed that S-134 primarily inhibits CDK9 at the protein and cellular levels, respectively. The detailed mechanistic investigation demonstrated that the compound caused wild-type p53 stabilisation and cell cycle arrest at the G2/M transition. Cancer cell death induced by S-134 was proven by Annexin-V/PI staining, caspase-3 assay and PARP cleavage. Transcription and expression of anti-apoptotic proteins Mcl-1, Bcl-2 and XIAP were reduced by the inhibitor, as proved by RT-PCR and Western blots respectively. Compound 2-methoxy-5-(3,4,5-trimethoxyphenethyl)phenyl 2,2,5,5-tetramethyl-2,5-dihydro-1H-pyrrole-3-carboxylate-N-oxide (ZJU-6, 6g) a semi-synthetic derivative of the natural medicinal compound Erianin (6a) was designed to introduce anti-oxidant property and enhance anti-angiogenic activity of Erianin. The study of ZJU-6 revealed that while the effect of cellular growth inhibition and the transcription of Bcl-2 were reduced by the structural modification, the suppression of tubulin polymerisation and anti-angiogenic properties were enhanced compared to Erianin. Compound BI 2536, 4-(8-cyclopentyl-7-ethyl-5-methyl-6-oxo-5,6,7,8-tetrahydropteridin-2-ylamino)-3-methoxy-N-(1-methylpiperidin-4-yl)benzamide (10), is one of the most potent and selective inhibitors of Polo-like kinase 1 (Plk1) and is a current experimental candidate for the treatment of cancer. A racemic BI 2536 was synthesised using multiple synthesis routes, which aimed to use as a lead compound for the discovery of novel Plk1 inhibitors.